Combination Therapies with Y90: Immunoradiation - Deipolyi, Amy R.; Johnson, Christopher Bryce; Erinjeri, Joseph P.; Bryce, Yolanda C.D. (Digestive Disease Interventions, 2020)
While much progress has been made in oncologic care, metastatic solid organ cancer still carries a poor prognosis. Immunotherapy has emerged as a promising approach, though in most patients, does not control disease when given as a monotherapy. Combining immunotherapy with locoregional therapy is one approach to boost the efficacy of treatments and potentially prolong survival. Most of the researches regarding combination therapies have involved external radiation. This review describes the immunologic effects of external radiation and radioembolization, and how these effects provide a rationale for combining hepatic radioembolization with immunotherapy.
Keywords: immunotherapy; radiation; radioembolization; abscopal effect